Analisis Anggaran Pendapatan Dan Belanja Daerah Kabupaten Kutai Kartanegara Tahun 2010 Sampai 2014 - Suprapto, Heru (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2016)
The reaserch Regional Govermance Budget Analysis or (APBD) inKutai Kartanegara Regencyused data series Regional Govermance Revised Budget Analysis or (APBD-P) during 2010 until 2014. APBD-P was chosen becauseit has better accuracy prediction than the Regional Govermance Budget aproach or (APBD). The methods used descriptive analysis of APBD-P ratio. The results of RevenuesAnalysis showed that fiscal space conditions was diminishing,it’s mean flexibility of Kutai Kartanegara Regency to spending on activities priority was decreases. On the Government ExpendituresAnalysis, showed the Personnel Expenditure had increasing trend, especially since the Additional Income SupportPolicy (Kebijakan Tunjangan Tambahan Penghasilan) was appliedin2011. On the Financing analysis, deficit spending from many yearswas increasing although it’scovered byUnspent Funds At End Of Fiscal Years (Sisa Lebih Penggunaan Anggaran/SiLPA), it shows the weakness of the planning and implementation.Keywords: APBD, fiscal space, Personnel Expenditure